Management of Development of Madrasah Aliyah Plus Skills In Increasing Competitiveness In The Society 5.0 Era (Multicite Study at Madrasah Aliyah Negeri Plus Skills In Langkat District) - Syahputra, Muhammad Rizki; Nasution, Wahyudin Nur; Mesiono, Mesiono (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study aims to analyze the development management of madrasah aliyah plus skills in increasing competitiveness in the era of society 5.0. This research is a multisite study on MAN plus Skills in Langkat District. This research uses a qualitative approach with a multi-site study type. The results of the study show that (1) the planning of the Langkat District Plus Skills Aliyah Aliyah in Increasing Competitiveness in the Society 5.0 Era by providing skills programs as a form of additional cross-interest learning at the Plus Skills Madrasah Aliyah. 6 (six) hours per week. (3) Model for the Development of Langkat District Madrasah Aliyah Plus Skills in Increasing Competitiveness in the Era of Society 5.0, that Langkat 1 State Madrasah Aliyah Plus Skills provides students with 3 (three) types of Skills such as 1) Automotive Engineering, 2) Computer and Network Engineering , and 3) Fashion Design, then Madrasah Aliyah Negeri 3 Langkat Plus Skills also equips students with 3 (three) types of Skills such as: 1) Computer and Network Engineering, 2) Multi Media, 3) Graphic Design.